Various guest PAHs locked into a soft-cavity-type host assembled via halogen bonds to form luminescent cocrystals. Issue 34 (13th August 2020) - Wu, Wen Xin; Wang, Hui; Jin, Wei Jun
Abstract : Host chains assembled from 1, 4-DITFB and PPNO mainly using C–I⋯ − O–N + halogen bonds present a remarkable capacity to accommodate PAHs of various sizes, and the generated host–guest ternary cocrystals exhibit diverse luminescence properties. Abstract : Luminescence of polyaromatic hydrocarbons (PAHs) is quenched easily owing to their dimerization or tightly packed structures in the crystal state. In the current work, a soft-cavity-type host assembly of 1, 4-diiodotetrafluorobenzene and 4-phenylpyridine N -oxide using halogen bonds was produced, and single isolated PAH guests were encapsulated in the host cavities to form ternary host–guest cocrystals. The thickness of the host cavity was observed to vary significantly, useful for accommodating various PAHs with different sizes, and it increased from 3.3 to about 6.7 Å when the guest was changed from pyrene, triphenylene, or fluoranthene to the relatively large perylene or benzo[ a ]anthracene molecule. The luminescence behaviors of PAHs in the ternary host–guest cocrystals originated from discrete PAH molecules and were also tuned by intermolecular interactions to a certain degree, and the materials displayed purple-pink, light-pink, jewelry-blue, yellow-green and amaranth emissions, respectively, at room temperature.